Revealing the critical role of in-situ plant and microbe community structure in remediation of typical high-arsenic soil through molecular analysis - Zhou, Min; Shi, Feng; Li, Xinru; Su, Hailei; Wei, Yuan; Wang, Fanfan (Frontiers in Plant Science, 2025)
In situ plant–fungal combined remediation technology for arsenic (As)-contaminated soil has emerged as a dominant technology in soil pollution remediation both domestically and internationally. However, the lack of systematic studies on in situ plants and rhizosphere fungal diversity in As-contaminated soils, particularly in heavily polluted area, limits the application of the plant–fungal combined remediation technology. In this study, we surveyed and identified the distribution of dominant native plant in highly arsenic-contaminated area, and then we used 18S rDNA technology to analyze the diversity of rhizosphere fungi and related factors from the area. The results revealed that Pteris vittata (L.) of Pteridaceae and Imperata cylindrica (L.) Beauv. of Poaceae are the dominant native plants in highly arsenic-contaminated area. The concentrations of As in the rhizosphere soils of the dominant plants in the area exceeded the As soil limits set by the European Union and the World Health Organization. A large quantity of As resulted in the dominance of fungi from the phyla Glomeromycota, Ascomycota, and Basidiomycota in the contaminated area soils, while relative abundance of fungi is varied in different sites. Additionally, soil acidity and alkalinity (pH), available phosphorus (AP), and As had the most notable effects on fungal diversity in Shihuangsi village and Linkuang village, whereas the low soil organic carbon (SOC) content in Heshan village was the primary limiting environmental factor for fungal diversity. The results of this study provide a theoretical foundation and technical guidance for the development of novel plant–fungal combined remediation technologies aimed to the control of As pollution in plant and soil.